2008
DOI: 10.1063/1.2919134
|View full text |Cite
|
Sign up to set email alerts
|

Ionic correlations in the inhomogeneous atmosphere surrounding cylindrical polyions: Catalytic effects of polyions

Abstract: The structural properties of linear polyelectrolyte solutions in the presence of a salt as evidenced through ionic correlations in the inhomogeneous atmosphere around a polyion and their consequence such as the catalytic potential are studied by using Monte Carlo simulation techniques. The simulations are performed on the cylindrical cell model where a uniformly charged hard cylinder mimics the linear polyion, which is caged in its own cylindrical cell containing counterions and salt. The cell (volume) average… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…The reverse trend is believed to be a consequence of the fact that the strongly hydrated fluoride anions do not release their hydration water when interacting with 3,3-ionene [50,51]. The endothermic effect, qualitatively correctly predicted by the continuum solvent theories [35,37], can therefore be explained by the electrostatic screening due to the added electrolyte. (5) The magnitude of the heat effects in Figures 2 and 3 followed the series NaF < NaCl < NaBr < NaI at all temperatures, i.e.…”
Section: Calorimetric Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…The reverse trend is believed to be a consequence of the fact that the strongly hydrated fluoride anions do not release their hydration water when interacting with 3,3-ionene [50,51]. The endothermic effect, qualitatively correctly predicted by the continuum solvent theories [35,37], can therefore be explained by the electrostatic screening due to the added electrolyte. (5) The magnitude of the heat effects in Figures 2 and 3 followed the series NaF < NaCl < NaBr < NaI at all temperatures, i.e.…”
Section: Calorimetric Resultsmentioning
confidence: 81%
“…It was shown that aqueous ionene solutions exhibit strong specific ion effects, where replacing one counterion species by another may yield qualitatively different behaviour of the solution. For example, diluting a solution of 3,3-ionene fluoride with water yields an exothermic effect [26] (in accord with continuum solvent theories [33][34][35][36][37]) but upon addition of water to 3,3-ionene chlorides, bromides, and iodides heat is consumed [26,30]. Furthermore, heat effects upon dilution depend on the hydrophobicity (charge density) of the ionene as well [26,30].…”
Section: Introductionmentioning
confidence: 87%
“…Indeed, similar error cancellations in applications of the mean field Poisson–Boltzmann theory in polyelectrolyte literature have long been known. We refer the reader to ref 33. for a recent account.…”
Section: Resultsmentioning
confidence: 99%
“…The third pair distribution function, shown in figure 5 (a)-(c), describes the counterion-counterion correlation, g cc (r). In several recent papers [35][36][37][38], this distribution function has been extensively studied for the cylindrical model with infinitely long polyion. A strong increase of concentration of equally charged counterions in the vicinity of the polyion forms a basis of the catalytic effect [39,40].…”
Section: Flexible Oligoionsmentioning
confidence: 99%
“…As found in previous studies of infinitely long and rigid polyions [36], smaller ionic size yields stronger correlation between the counterions in the electrical double-layer. This counterion-counterion correlation is neglected in the Poisson-Boltzmann theory but as shown before [35] (see also the references therein), this is not considered to be a serious source of error when monovalent counterions are present in solution. For divalent counterions this is not true any more.…”
Section: Rigid Versus Flexible Oligoionsmentioning
confidence: 99%